UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH - BERTHA DIMARA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Efforts to increase Teacher Professional Competence through the Implementation of Principal Academic Supervision have been carried out at SD Inpres 42 Taman Ria, Manokwari Regency, West Papua Province, for the 2022/2023 Academic Year. This research is a School Action Research (PTS) with a qualitative descriptive approach. This study aims to analyze the professional competence of teachers from the aspect of mastery of material, concepts, structures, and scientific patterns that support subjects, mastery of competency standards and basic competencies and the ability to develop creatively taught learning materials. The data sources used are primary and secondary data. Primary data comes from interviews and class observations. Secondary data from observations of syllabus and lesson plans documents as well as other relevant documents. Data collection instruments used interview guides, observation sheets and documentation studies. Data analysis techniques used the Milles and Huberman model, namely data reduction, display and data verification. The results showed an increase in teacher professional competence after being supervised by the school principal, 68.18% (15 out of 22) succeeded in achieving the mastery indicator (? 80%) . There are 7 out of 22 teachers (31.82%) of whom are in the